Transmission Degradation of Femtosecond Laser Pulses in Opened Cone Targets - 刘峰 林晓宣 刘必成 丁文君 杜飞 李玉同 马景龙 刘晓龙 盛政明 陈黎明 鲁欣 董全力 王伟民 王兆华 魏志义 陈佳洱 张杰 (Plasma science & technology, 2012)
Irradiated by femtosecond laser pulses with different energies, opened cone targets behave very differently in the transmission of incident laser pulses. The targets, each with an opening angle of 71° and an opening of 5 μm, are fabricated using standard semiconductor technology. When the incident laser energy is low and no pre-plasma is generated on the side walls of the cones, the cone target acts like an optical device to reflect the laser pulse, and 15% of the laser energy can be transmitted through the cones. In contrast, when the incident laser energy is high enough to generate pre-plasmas by the pre-pulse of the main pulse that fills the inner cone, the cone with the plasmas will block the transmission of the laser, which leads to a decrease in laser transmission compared with the low-energy case with no plasma. Simulation results using optical software in the low-energy case, and using the particle-in-cell code in the high-energy case, are primarily in agreement with the experimental results.